2014
DOI: 10.1002/nau.22682
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of neurogenic stress urinary incontinence: A systematic review of quality assessment and surgical outcomes

Abstract: The quality of evidence obtained from non-RCTs is modest. Surgeries for NSUI have relatively high success rates but also high complication rates in this highly heterogeneous population. More studies using modern techniques are required to update our knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 19 publications
0
45
0
1
Order By: Relevance
“…Men treated with ProACT for nSUI, showed a lower level of efficacy than non‐neurogenic patients. Reductions in efficacy between non‐neurogenic and neurogenic patients are also seen with the AUS and male sling . Studies on ProACT also suggest that patients with prior radiation have lower efficacy results than nonirradiated patients .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Men treated with ProACT for nSUI, showed a lower level of efficacy than non‐neurogenic patients. Reductions in efficacy between non‐neurogenic and neurogenic patients are also seen with the AUS and male sling . Studies on ProACT also suggest that patients with prior radiation have lower efficacy results than nonirradiated patients .…”
Section: Discussionmentioning
confidence: 97%
“…Reductions in efficacy between non-neurogenic and neurogenic patients are also seen with the AUS and male sling. 33 Studies on ProACT also suggest that patients with prior radiation have lower efficacy results than nonirradiated patients. 13,15,16,21 and have a higher risk of urethral erosion.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been the standard and preferred option for the treatment of non-neurogenic stress urinary incontinence (SUI), 2 and most successful in treatment of neurogenic SUI. 3 However, AUS has been associated with high revision rates-up to 26%. 2 The impact of prior radiotherapy (RT), 4,5 previous AUS, 6 and erosion and/or infection of previous AUS 7 on the surgical outcomes of AUS was investigated in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…In general, urinary incontinence is common among SCI patients; however, we found that the utilization of urologic reconstruction/urinary diversion surgeries (including stress incontinence procedures) is low. With further follow‐up, progressive neurogenic bladder dysfunction, and failure of more conservative treatment options, the use of these procedures may increase . While prior case series have reported treating SUI primarily in SCI patients with lumbar lesions, it is likely that many of the urologic reconstruction procedures were done for patients with cervical lesions and severe intrinsic sphincter deficiency, urethral destruction from indwelling catheters, or as part of more complex reconstruction.…”
Section: Discussionmentioning
confidence: 99%